2018
DOI: 10.1186/s12886-018-0941-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of aqueous humor from patients with drusen and reticular pseudodrusen in age-related macular degeneration

Abstract: BackgroundTo identify novel biomarkers related to the pathogenesis of dry age-related macular degeneration (AMD), we adopted a human retinal pigment epithelial (RPE) cell culture model that mimics some features of dry AMD including the accumulation of intra- and sub-RPE deposits. Then, we investigated the aqueous humor (AH) proteome using a data-independent acquisition method (sequential window acquisition of all theoretical fragment ion mass spectrometry) for dry AMD patients and controls.MethodsAfter uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Although proteins in AH are present in relatively low concentrations when compared to blood plasma, they are vital in the maintenance of anterior segment homeostasis [ 2 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Previous studies have shown significant alterations in several proteins in the AH obtained from eyes with glaucoma [ 12 , 13 , 14 , 15 , 20 , 21 ] and other eye disorders, including age-related macular degeneration [ 14 , 16 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although proteins in AH are present in relatively low concentrations when compared to blood plasma, they are vital in the maintenance of anterior segment homeostasis [ 2 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Previous studies have shown significant alterations in several proteins in the AH obtained from eyes with glaucoma [ 12 , 13 , 14 , 15 , 20 , 21 ] and other eye disorders, including age-related macular degeneration [ 14 , 16 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of RPD has been associated with major AMD risk polymorphisms in ARMS2/HTRA1 genes [24,49,50]. RPD are located in the subretinal space and share compositional similarities with conventional drusen, yet their lipid composition is different than soft drusen [51][52][53][54][55]. Nevertheless, RPD appear also in other retinal diseases such as Sorsby fundus dystrophy and pseudoxanthoma elasticum, and a common pathogenetic pathway involving BrM and RPE interface is possible [56].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, RPD appear also in other retinal diseases such as Sorsby fundus dystrophy and pseudoxanthoma elasticum, and a common pathogenetic pathway involving BrM and RPE interface is possible [ 56 ]. In a recent study, RPD patients were reported to have different AH protein profiles in comparison with patients with soft drusen [ 55 ]. In the same study, it was speculated that RPD formation is linked to a dysfunctional RPE, which secretes proteins aberrantly towards the apical surface instead of onto basolateral surface leading to the accumulation of deposits in subretinal space [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Je-Hyun Baek et al used SWATH-MS technology to quantify differentially expressed proteins in the AH between patients with drusen and reticular pseudodrusen (RPD) of age-related macular degeneration (AMD). In three newly discovered dry AMD-related proteins, LUM and KERA were upregulated in both RPD and soft drusen, and these are correlated to the extracellular matrix organization (Baek et al, 2018). Chiang SY et al used MALDI-TOF MS and identified 11 AH proteins with a pathophysiological role in diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%